Predictability of Duolingo English mock test for Chinese college-level EFLs: using assessment use argument - Ma, Xinyi; Zhang, Haomin (Frontiers in Education, 2024)
Online international language tests have been gaining popularity since the COVID-19 pandemic. This study explored the predictive ability of the mock test of Duolingo English Test (DET) for Chinese students. College-level EFLs (N = 42) participated in this study and completed the official online mock test. Through quantitative analysis, the findings demonstrated that mock scores were significantly correlated with TOEFL or IELTS results. However, given that the mock test scores are significantly lower than expected, the consequential validity needs further analysis. Using Assessment Use Argument in qualitative analysis, the study established the claim, warrants, evidence, and potential rebuttals regarding the consequential validity of Duolingo English mock test. With further analysis on test specification, the characterization of Target Language Use domain of DET reading test items were investigated. The results indicate that although the DET mock test is relatively more accessible, it needs modification to become more suitable for Chinese EFLs. Suggestions and limitations on Chinese students using DET and its mock test were also discussed.